Bidens pilosa L. (Asteraceae) control in sunflower with residual herbicides - Brighenti, Alexandre Magno (Comunicata Scientiae, 2019)
One of the most damaging species in sunflower crops in Brazil is the hairy beggartick (Bidens pilosa L). The large number of seeds, the various vegetative cycles during the year, the staggered germination and the scarcity of selective and effective herbicides to control this weed in sunflower are some of attributes that hinder the control of hairy beggartick populations. Two experiments were carried out to evaluate the control of hairy beggarticks, as well as sunflower tolerance to herbicides. The treatments were as follows: S-metolachlor (1,200 and 2,400 g ai ha-1), flumioxazin (60 and 120 g ai ha-1), and sulfentrazone (150 and 300 g ai ha-1) and two controls (weedy and weed-free check). The selectivity of the herbicides was higher at low doses. Flumioxazin and sulfentrazone caused injury to sunflowers at the highest doses and mainly in sandy soils. Although S-metolachlor did not cause visual symptoms of injury, the higher dose reduced sunflower yield. The herbicides sulfentrazone and flumioxazin provided satisfactory control of hairy beggartick plants in both types of soils. S-metolachlor presented medium control of hairy beggarticks in clay soil; however, its efficiency was slightly higher when applied in sandy soil. The most efficient herbicide for controlling hairy beggartick plants was flumioxazin, followed by sulfentrazone.